Women coaches leadership development programme: an evaluation study of programme effectiveness - Jowett, Sophia; Slade, Katelynn; Gosai, Jyoti; Davis, Louise (Frontiers in Sports and Active Living, 2024)
Introduction Women's sport has been experiencing continuous growth, yet the low levels of women coaches in the United Kingdom (UK) suggests that the sport is missing out on potential talent. Guided by empirical research, a women-only leadership development programme was designed and implemented by UK Sport to a cohort of 20 coaches from January to June 2021. The main characteristics of the programme included raising awareness of gender bias while at the same time focusing on women coaches' leadership purpose and skills within a safe environment that supports coaches to build their leader identity. Methods Kirkpatrick's (1998) four-level model was employed to guide the evaluation of programme effectiveness: reactions, learnings, applications and results. Interviews were conducted with 17 participating coaches. Results Content analysis of the qualitative data revealed five general categories (a) evaluations were mainly positive highlighting the aspects of the programme they liked, enjoyed and made most impression onto them; (b) learnings that impacted their work directly and immediately emerged as was the importance of on-going development; and (c) the majority of the women desired progression and transitioning to senior coach leadership positions was felt within their grasp; nonetheless, (d) challenges emerged and were described as organisational (e.g., recruitment, remuneration) and personal (e.g., work-life balance, childcare). Discussion Overall, the effectiveness of the programme was captured in its capacity to raise awareness, develop knowledge, build connections, and inspire so much so that its effects translated to many of these women moving to more senior leadership positions post-programme. Practically, this evaluation highlights that investment in individual coaches is part of the systemic change required to bring about gender balance in the coach workforce.